Do Audit Committee Attributes Moderate Sustainability Reporting’s Impact On Firm Performance? - Nidhi Mittal (Journal of Governance and Accountability Studies, 2026)
Purpose: Sustainability reporting has been frequently used globally to provide corporate transparency to stakeholders on environmental, social, and governance matters. Therefore, this study investigates how audit committee attributes act as moderators on sustainability reporting and firm performance relationships in India. Research Methodology: This research employs the DWH Test for Endogeneity and OLS regression on data collected from the listed BSE 500 companies, with 840 observations from March 2019 to 2024. It takes ESGScore as independent, ACMeet and ACSize as moderators, and RONW and Tobin’s q as dependent variables. Results: The empirical results indicate a significant positive association between firm performance and ESG reporting. They also show a moderation effect of AC Size (p-value-0.06) and AC Meeting (p-value-0.00) on the relationship between RONW and ESG, implying that good audit management increases the benefits of sustainability projects. Conclusions: It indicates the high trust of stakeholders which improves corporate reputation, creates brand value and drive innovation to gain competitive advantage and long-term growth which leads to positive IRR and helps in managing the various potential risks causing by environmental and societal factors. Limitations: This study considers only two  AC attributes and depends on secondary ESG data, thus there may be chance of potential bias and unobserved variables. Contribution: This research contributes in terms of describing the deeper insights into governance quality by introducing AC size and AC meetings as moderators on ESG reporting and FP relationship.